Women on The Text According To Amina Wadud Muhsin in Qur’an and Women - Abu Bakar (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2018)
This article explains hermeneutic concept of Amina Wadud stating that men and women are equal. It is based on the interpretation of both Qur'anic keywords (nafs, min and azwaj) and Qur'anic concepts (qiwamah, angel and nusyuz). Wadud reasoned that those key words and concepts were, unfortunately, red partially by most of commentators and resulted gender biased exegetical works. Using the method of descriptive and critical, this article aims to elaborate how Wadud argued against the pathriarcal  exegesis of the Qur’an in her book, Qur’an and Women. At the conclusion, it is found that Wadud criticized the biased works using two steps of hermeneutical approach. The first is by examining on how The Qur’an mentions some relating issues and second is by creating generalization on special respons about historical background